The Role of Air Pollution Exposure and GSTM1-/GSTT1-Null Genotypes in Gestational Diabetes Mellitus Development: A Case–Control Study on Gene–Environment Interactions - Ana Susa; Dragana Davidovic; Nadja Nikolic; Tamara Sljivancanin Jakovljevic; Vera Kujundzic; Sladjana Mihajlovic; Ljiljana Bogdanovic (Antioxidants)
As gestational diabetes mellitus (GDM) rises as a major public health concern, various factors have been identified as potential contributors, with air pollution drawing increasing attention. The mechanisms by which air pollutants lead to detrimental impacts are largely attributed to oxidative stress. However, the role of air pollution is still not entirely clarified, suggesting that additional factors, such as genetic variability, particularly of genes involved in redox homeostasis, influence the GDM risk. This study addresses three questions: (1) whether ambient PM2.5, PM10, O3, and NO2 exposures associate with GDM risk; (2) if GSTM1-/GSTT1-null genotypes affect the risk of GDM; and (3) whether these genotypes modify pollution–GDM associations. This case–control study comprised 133 women in the case group and 144 in the control group. Exposure to air pollutants was assessed based on the participants’ residential addresses and during different time windows: pre-pregnancy period, first trimester, and second trimester. GSTM1/GSTT1 genotyping was conducted from blood samples. Higher PM2.5, PM10, and O3 levels increased GDM risk in women. While GSTM1-/GSTT1-null genotypes showed no overall link to GDM, non-smokers with GSTM1-null had higher GDM risk when exposed to PM2.5 during the first trimester. While further research on gene–environment interactions is needed, our findings highlight that reducing air pollution may lower GDM risk.